Designed Intercalators for Modification of DNA Origami Surface Properties. Issue 26 (14th May 2015) - Brglez, Josipa; Nikolov, Pavel; Angelin, Alessandro; Niemeyer, Christof M.
Abstract The modification of the backbone properties of DNA origami nanostructures through noncovalent interactions with designed intercalators, based on acridine derivatized with side chains containing esterified fatty acids or oligo(ethylene glycol) residues is reported. Spectroscopic analyses indicate that these intercalators bind to DNA origami structures. Atomic force microscopy studies reveal that intercalator binding does not affect the structural intactness but leads to altered surface properties of the highly negatively charged nanostructures, as demonstrated by their interaction with solid mica or graphite supports. Moreover, the noncovalent interaction between the intercalators and the origami structures leads to alteration in cellular uptake, as shown by confocal microscopy studies using two different eukaryotic cell lines. Hence, the intercalator approach offers a potential means for tailoring the surface properties of DNA nanostructures.